Alkaline phosphatase in metastatic castration-resistant prostate cancer: reassessment of an older biomarker. (21st June 2018) - Heinrich, Daniel; Bruland, Øyvind; Guise, Theresa A; Suzuki, Hiroyoshi; Sartor, Oliver
Since most patients with metastatic castration-resistant prostate cancer (mCRPC) have bone metastases, it is important to understand the potential impact of therapies on prognostic biomarkers, such as ALP. Clinical studies involving mCRPC life-prolonging agents (i.e., sipuleucel-T, abiraterone, enzalutamide, docetaxel, cabazitaxel, and radium-223) have shown that baseline ALP level is prognostic for overall survival, and may be a better prognostic marker for overall survival than prostate-specific antigen in patients with bone-dominant mCRPC. Mechanism of action differences between therapies may partly explain ALP dynamics during treatment. ALP changes can be interpreted within the context of other parameters while monitoring disease activity to better understand the underlying pathology. This review evaluates the current role of ALP in mCRPC.